2020
DOI: 10.3389/fbioe.2020.591467
|View full text |Cite
|
Sign up to set email alerts
|

Building Osteogenic Microenvironments With Strontium-Substituted Calcium Phosphate Ceramics

Abstract: Bioceramics have experienced great development over the past 50 years. Modern bioceramics are designed to integrate bioactive ions within ceramic granules to trigger living tissue regeneration. Preclinical and clinical studies have shown that strontium is a safe and effective divalent metal ion for preventing osteoporosis, which has led to its incorporation in calcium phosphate-based ceramics. The local release of strontium ions during degradation results in moderate concentrations that trigger osteogenesis wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 70 publications
0
16
0
2
Order By: Relevance
“…Due to limitations in reconstructing critical bone defects, developing bioactive scaffolds for bone tissue engineering has become an alternative strategy for skeletal reconstruction [ 20 , 43 ]. Among all these scaffolds, synthetic bioactive ceramics, such as hydroxyapatite, β-TCP, calcium polyphosphate, and biphasic calcium phosphate, are widely used as basic bone repair materials due to their excellent osteoconductive features and controllable chemical reagent deposition process [ 44 ]. Although some osteogenic biomacromolecules, such as recombinant human bone morphogenetic protein-2 (rhBMP-2), have been successfully loaded into these ceramics, serious side effects associated with ectopic or unwanted bone formation in certain situations have caused the Food and Drug Administration (FDA) to be increasingly cautious in approving the application of such materials [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to limitations in reconstructing critical bone defects, developing bioactive scaffolds for bone tissue engineering has become an alternative strategy for skeletal reconstruction [ 20 , 43 ]. Among all these scaffolds, synthetic bioactive ceramics, such as hydroxyapatite, β-TCP, calcium polyphosphate, and biphasic calcium phosphate, are widely used as basic bone repair materials due to their excellent osteoconductive features and controllable chemical reagent deposition process [ 44 ]. Although some osteogenic biomacromolecules, such as recombinant human bone morphogenetic protein-2 (rhBMP-2), have been successfully loaded into these ceramics, serious side effects associated with ectopic or unwanted bone formation in certain situations have caused the Food and Drug Administration (FDA) to be increasingly cautious in approving the application of such materials [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strontium and calcium (Ca) in bones have similar cellular and physiochemical properties. Although the exact mechanism of Sr in bone is not clear, it has been proposed that Sr interacts with cellular targets by activating calcium-sensing receptor (CaSR) similar to Ca 2+ , thereby acting as a signaling transduction pathway related to Ca-driven regulation of bone metabolism [ 54 ]. The phosphatase activity (ALP) is one of the most commonly used markers for osteoblast differentiation, and the enzyme activity is considered a necessary prerequisite for bone mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…BCP is a mixture of HA and β-TCP depending on different mixing ratios that can improve degradation and it has been reported that a 60:40 ratio of HA to TCP might provide an optimal formulation with respect to bone resorption and final degradation ( Jelusic et al, 2017 ; Steffi et al, 2018 ). In addition, in order to enhance the osteogenic, angiogenic and antimicrobial properties of biomaterials, some drugs and biological agents can be incorporated into CaPs, but it was found that these bioactive components were only loaded on the surface of the material and showed a sudden release effect which had no long-term therapeutic effect for body, thus a way to incorporate trace elements into CaPs to obtain a more durable release and safe was created ( Wan B. et al, 2020 ). Sr 2+ is widely incorporated into CaPs due to its dual role of enhancing osteoblast activity and inhibiting osteoclast proliferation.…”
Section: Strontium-doped Biomaterialsmentioning
confidence: 99%